RANCANG BANGUN ALAT MONITORING SUHU DAN POLUSI KARBON MONOKSIDA (CO) DI WILAYAH TEMBALANG BERBASIS INTERNET OF THINGS (IOT) - Hanifudin Tahier, Ahmad Ridlo; Rifqi Khairullah Muhamad; Daffa Maulana Fariza; Raihan Ramadhan; Yoga Reksandiko Rasyidin; Aprillia Ainun Rahmi (JEAS (Journal of Educational and Applied Science), 2024)
Increased urban mobility and activity can generate increased gaseous and particulate emissions, which can have an impact on air quality and public health. Therefore, it is important to understand environmental conditions in depth and develop innovative solutions to monitor and address environmental affects in Semarang City. The design of a monitoring tool for temperature and carbon monoxide (CO) pollution in the Tembalang area based on the Internet of Things (IoT) is the focus of the research which includes the application of NodeMCU ESP8266 technology, MQ-7 gas sensor, and DHT11 temperature sensor. This research focuses on learning basic concepts in developing IoT applications for environmental monitoring, with the main purpose of monitoring temperature and carbon monoxide pollution levels in the Tembalang area. During the research, the researchers observed the vehicle traffic being both busy and quiet. From the research data, the average value of temperature, humidity and CO gas levels at peak times were 31.4, 83.14% and 9.7 ppm, respectively. While in quiet traffic condition, the average values of temperature, humidity and CO gas levels are 29.8, 84.07% and 1.67 ppm, respectively. In addition, this research also successfully displays data online through the Thingspeak online platform which can be accessible to the public from anywhere through the website.